2023
DOI: 10.3390/ani13081425
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography as a Potential Non-Invasive Tool for Estrus Detection in Cattle and Buffaloes

Abstract: The productivity of dairy animals has significantly increased over the past few decades due to intense genetic selection. However, the enhanced yield performance of milk animals caused a proportional increase in stress and compromised reproductive efficiency. Optimal reproductive performance is mandatory for the sustainable production of dairy animals. Reproductive efficiency is marked by proper estrus detection and precise breeding to achieve maximum pregnancies. The existing conventional methods of estrus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Ongoing scientific endeavors are in place to develop cost-effective, user-friendly methods for estrus detection [23]. Estrus detection can be more accurate in precision livestock farming as mechanical monitoring gives real-time data [71].…”
Section: Sensors In Estrus Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing scientific endeavors are in place to develop cost-effective, user-friendly methods for estrus detection [23]. Estrus detection can be more accurate in precision livestock farming as mechanical monitoring gives real-time data [71].…”
Section: Sensors In Estrus Detectionmentioning
confidence: 99%
“…Automated estrus detection using sensors, infrared thermography and machine learning models is not limited to sows only. Considerable progress is evident in cow [141][142][143][144], buffalo [23,145], and ewe [146,147] estrus detection as well. Though installing and implementing real-time estrus detection systems may require an initial investment, in the long run, will result in benefits and significant cost savings for livestock farmers and industries.…”
Section: Benefits Of Technology and Ai-based Estrus Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal husbandry is not limited to raising animals; raising and breeding the difference lies in the objectives set [2]. Farming is carried out by business people seeking profit with the application of management principles to the factors of production that have been optimally combined [4]- [6]. The public demand for beef and milk has increased cattle business opportunities, and many people are starting to look at them, but problems such as losing livestock and capital to build cattle pens make some people reluctant to start a cattle business [1], [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…IRT tools were found to be cost-and time effective, reliable as well as non-invasive, while showing great potential for remote sensing and automatization in monitoring early indicators for health abnormalities in dairy cattle, being previously validated for mastitis and lameness detection (4,5). Moreover, several recent studies had found IRT as a feasible tool to evaluate thermal stress (6)(7)(8) and reproduction (9,10) in cattle. Additionally, both putatively negative and positive emotions have been shown to induce physiological responses in cattle, that allows indirect assessment of the sympathetic and parasympathetic activity via the alterations in temperature of different body areas, caused by phenomena such as stress-induced hyperthermia (11).…”
Section: Introductionmentioning
confidence: 99%